Immobilization of dimethylamine and aniline using soft lignocelluloses material (abelia chinensis sawdust) for controlling striga hermonthica in sorghum field - Lazwan, Rindap; Daben, Janet; Agbalaga, Rechit; Dashak, Dayil (International Journal of Advanced Chemistry, 2017)
Chemical modifications of lignocelluloses materials are advance development that are fast and convenient to convert the low value woody residues to create channels for controlling the release of organic manure to proffer solutions to farmers in the increasing soil acidity, rapid weed's growth, soil infertility and food scarcity. The study investigates the physic-chemical parameters, and the effect of immobilized nitrogenous bases on oxidized sawdust for controlling Striga hermonthica in the sorghum field. The results indicate that the moisture content increases with increase particle size as water absorption capacity increases with time and size, thereby, ash content decrease with increase size. The control, oxidized and immobilized sawdusts were analyzed using FT-IR and it was clear that pretreated sawdust of 0.08-0. 10M KIO4 oxidized the exposed hydroxyl groups of the lignocelluloses material to the carbonyl group but were unable in 0.04-0.06M KIO4. Likewise, the absorption bands showed that the nitrogenous bases were incorporated while carbonyl absorptions were still observed. The effect of immobilized Dimethylamine concentrations on gradual release on sorghum grows progressively with the absence of S. hermonthica while aniline grows faster than Dimethylamine at 0.5-1.0M then diminished at 1.5M than Dimethylamine. The application of immobilized amines on the sorghum field showed that this invention would enhance sorghum productivity through striga control.